Case Report: Pituitary Morphology and Function Are Preserved in Female Patients With Idiopathic Intracranial Hypertension Under Pharmacological Treatment - Tozzi, Rossella; Moramarco, Antonietta; Watanabe, Mikiko; Balena, Angela; Caputi, Alessandra; Gangitano, Elena; Petrangeli, Elisa; Mariani, Stefania; Gnessi, Lucio; Lubrano, Carla (Frontiers in Endocrinology, 2021)
Idiopathic Intracranial Hypertension is a neurological disorder primarily affecting overweight women of childbearing age. It is often characterized by radiologic evidence of empty sella (ES), which is in turn frequently associated with pituitary dysfunction, with the somatotropic axis most commonly affected. No recent evidence is available relative to the presence of pituitary hormone deficiencies in adult patients with Idiopathic Intracranial Hypertension (IIH) under pharmacological therapy. We therefore explored pituitary function and morphology in a small cohort of female patients with IIH treated with acetazolamide. Fifteen female patients aged 42 ± 13 years with IIH lasting between 12 and 18 months were evaluated. All patients were affected by recurrent headaches in addition to visual changes of variable severity. IIH diagnosis was made after exclusion of other causes of raised intracranial pressure, and a specific ophthalmological evaluation was conducted to assess for the presence of papilledema. No particular endocrinological disturbances were detected during the enrolment visits, except for a high obesity prevalence (87%, BMI 35.16 ± 8.21 kg/m2), one case of total thyroidectomy for papillary thyroid carcinoma and two patients with irregular menses and mild hirsutism. All the participants underwent a pituitary MRI with contrast, and two different operators performed pituitary measurements in coronal and sagittal scans for morphologic assessment. Blood samples for the anterior pituitary axis evaluation were collected, and the somatotropic axis was further evaluated with a GHRH + Arginine test; other dynamic tests were performed in case of suspected hormonal deficiency. Despite ES being found in 73% of the patients, pituitary volume was preserved, ranging from 213.85 to 642.27mm3 (389.20 ± 125.53mm3); mean coronal pituitary height was 4.53 ± 1.33 mm. Overall, baseline anterior pituitary hormones levels were within normal ranges, and none of the patients with ES had an altered response to the GHRH + arginine stimulation test. We found one patient suffering from iatrogenic hyperthyroidism and two diagnosed with subclinical primary hypothyroidism due to Hashimoto’s thyroiditis. Two young patients were suspected of having polycystic ovary syndrome, and they were therefore further investigated. In conclusion, this case series shows that, despite the high prevalence of ES, the pituitary function of IIH patients treated with acetazolamide is preserved. To date, there is no evidence regarding the trend over time or upon treatment discontinuation in regard to the pituitary function of patients with IIH, and it is therefore not possible to infer whether our finding would be replicable in such settings. We therefore suggest an endocrine follow-up over time in order to monitor for potential pituitary dysfunction.